Novel fluorescent (p-Phenylene ethynylene)-Calix[4]arene- based polymer: design, synthesis, and properties - Costa, Alexandra I. (2020)
A novel ﬂuorescent (p-phenylene ethynylene)-calix[4]arene-based polymer (CALIX-PPE) has been successfully synthesized by cross-coupling polymerization of bis-calix[4]arene 1 with 1,4-diethynylbenzene. The polycondensation was carried out in toluene/NEt3 at 35 8C for 24 h, using PdCl2(PPh3)2/CuI as the catalytic system, furnishing CALIX-PPE in excellent isolated yields (higher than 95%, several runs). The yellow polymer is freely soluble in several nonprotic organic solvents. The GPC trace of the isolated polymer showed a monomodal distribution and a number-average molecular weight of 23,300 g mol-1 (Mw/Mn¼ 2.05). No evidence was found in the structural analysis (FTIR and 1H/13C NMR) regarding the formation of alkyne homocoupled segments along the polymer chain. For comparative purposes, the syn- thesis of an analogous poly(p-phenylene ethynylene) containing p-t-butyl-phenoxy- methyl side chains (TBP-PPE) was also undertaken. A great similarity was found between the photophysical properties of CALIX-PPE and TBP-PPE in solution (UV–vis and laser induced luminescence), clearly demonstrating their unique de- pendence on the structure and conformation of the conjugated PPE backbone. The ﬂuorescence spectra of polymers are of nearly identical shape, displaying their maxi- mum emission around 420 nm. The calculated solution photoluminescence quantum yields of CALIX-PPE and TBP-PPE are of similar magnitude (Ø/F(CALIX-PPE) = 0.43; Ø/F(TBP-PPE) = 0.51).